2005
DOI: 10.1091/mbc.e04-05-0434
|View full text |Cite
|
Sign up to set email alerts
|

ERdj3, a Stress-inducible Endoplasmic Reticulum DnaJ Homologue, Serves as a CoFactor for BiP's Interactions with Unfolded Substrates

Abstract: We recently identified ERdj3 as a component of unassembled immunoglobulin (Ig) heavy chain:BiP complexes. ERdj3 also associates with a number of other protein substrates, including unfolded light chains, a nonsecreted Ig light chain mutant, and the VSV-G ts045 mutant at the nonpermissive temperature. We produced an ERdj3 mutant that was unable to stimulate BiP's ATPase activity in vitro or to bind BiP in vivo. This mutant retained the ability to interact with unfolded protein substrates, suggesting that ERdj3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
193
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(209 citation statements)
references
References 60 publications
11
193
0
Order By: Relevance
“…In the present study, deletion of the J domain abrogated interaction of ERdj4 with BiP but not with misfolded SP-C; in fact, interaction of misfolded SP-C with ERdj4 was consistently enhanced by deletion of the J domain or mutation of the HPD motif. This finding is similar to that reported for interaction of ERdj3 with unfolded substrates (Shen and Hendershot, 2005) and suggests that the C-terminal domain containing the Gly/Phe-rich region may bind unfolded/misfolded substrate directly. This hypothesis is also supported by the observation that yeast Sis1p directly binds substrate through its C-terminal domain and suggests that type II DnaJ proteins may have chaperone activity independently of BiP (Lu and Cyr, 1998).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, deletion of the J domain abrogated interaction of ERdj4 with BiP but not with misfolded SP-C; in fact, interaction of misfolded SP-C with ERdj4 was consistently enhanced by deletion of the J domain or mutation of the HPD motif. This finding is similar to that reported for interaction of ERdj3 with unfolded substrates (Shen and Hendershot, 2005) and suggests that the C-terminal domain containing the Gly/Phe-rich region may bind unfolded/misfolded substrate directly. This hypothesis is also supported by the observation that yeast Sis1p directly binds substrate through its C-terminal domain and suggests that type II DnaJ proteins may have chaperone activity independently of BiP (Lu and Cyr, 1998).…”
Section: Discussionsupporting
confidence: 89%
“…Expression of another ER-localized DnaJ homologue, ERdj3, was also modestly increased (1.9ϫ) in cells expressing mutant SP-C (Table 1). ERdj3 was shown previously to be robustly increased in response to treatment with the ER stress-inducing agents tunicamycin or thapsigargin, associated with both unfolded and mutant protein substrates (Shen and Hendershot, 2005), and it was identified as a direct target of spliced XBP-1 (Kanemoto et al, 2005;Shen and Hendershot, 2007). However, ERdj3 did not associate with either WT or mutant SP-C (Supplemental Figure S5).…”
Section: Discussionmentioning
confidence: 87%
“…33 ERdj3 associates directly with nascent unfolded proteins in an Hsp70-independent manner, then recruits Hsp70/BiP, and finally dissociates from the nascent unfolded proteins. 14,34 These results indicate that ERdj3 serves to inhibit protein aggregation until BiP joins the complex. 14 Recently, it was reported that ERdj3 is associated with the Sec61 translocon.…”
Section: Erdj3bmentioning
confidence: 88%
“…ERdj4, which is required for degradation of misfolded proteins, 13 is membraneanchored via its uncleaved signal peptide, with the remaining protein located in the ER lumen. 14,15 ERdj5 plays central roles in the degradation of misfolded proteins via its four thioredoxinlike domains (TRX) that contribute to reductase activity. [16][17][18] As mentioned above, organization of ERdjs is different in mammals, yeast and plants ( Fig.…”
Section: Gene Organization Of Erdjs In Different Organismsmentioning
confidence: 99%
“…These results point to a new functional assignment for p58 IPK in serving as a BiP cochaperone to optimize protein folding homeostasis in the ER. Because p58 IPK represents one among several (at least five others) ER localized Jdomain proteins that interface with BiP (Feldheim et al, 1992;Brightman et al, 1995;Shen et al, 2002;Hosoda et al, 2003;Shen and Hendershot, 2005), its absence would result in an ER lumen that is only modestly compromised in overall folding capacity. The functional consequences of this slightly lower protein maturation capacity would be obscured under all but the most taxing conditions and can explain each of the following phenotypic observations in cells and animals lacking p58 IPK .…”
Section: Discussionmentioning
confidence: 99%